2019
DOI: 10.1007/978-3-030-35888-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Coordination Supports a Sense of Commitment in Human-Robot Interaction

Abstract: In the current study, we presented participants with videos in which a humanoid robot (iCub) and a human agent were tidying up by moving toys from a table into a container. In the High Coordination condition, the two agents worked together in a coordinated manner, with the human picking up the toys and passing them to the robot. In the Low Coordination condition, they worked in parallel without coordinating.Participants were asked to imagine themselves in the position of the human agent and to respond to a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The studies demonstrated that subjects preferred to interact with the robot able to display such expressions than with the more efficient robot without such social capacities. On the other hand, we can find some studies that give support to the idea that some indications of motivation and commitments on behalf of the robot can boost the human feeling of obligation to remain committed to the action (Michael & Salice, 2017;Powell & Michael, 2019;Vignolo et al, 2019). In Vignolo et al's experiment, an iCub robot interacted with children in a teaching skills exchange.…”
Section: Emotional Robots and Commitmentsmentioning
confidence: 89%
“…The studies demonstrated that subjects preferred to interact with the robot able to display such expressions than with the more efficient robot without such social capacities. On the other hand, we can find some studies that give support to the idea that some indications of motivation and commitments on behalf of the robot can boost the human feeling of obligation to remain committed to the action (Michael & Salice, 2017;Powell & Michael, 2019;Vignolo et al, 2019). In Vignolo et al's experiment, an iCub robot interacted with children in a teaching skills exchange.…”
Section: Emotional Robots and Commitmentsmentioning
confidence: 89%
“…Mioch et al [10] is based on Singh's commitment model [11] to allow their participants to agree on which agent is committed to do a task for their joint plan. Vignolo et al [12] explored the commitment of the agents to achieve a task related to high or low space-temporal coordination, where they found that high coordination was related to a higher degree of commitment. Finally, Chang et al [13] presented an algorithm for Shared Cooperation that facilitates collaboration by promoting mutual responsiveness through three mechanisms: understanding the agents' intent, aligning their sub-plans, and providing assistants to the partner as needed.…”
Section: A Related Workmentioning
confidence: 99%
“…The idea that commitments and sense of joint agency are related has received indirect support from empirical evidence showing that perceived coordination or movement synchronization may bolster our sense of commitments (Michael et al, 2016; Vignolo et al, 2019). For instance, in a series of experiments, Michael et al (2016) presented a group of participants with different videos where two persons either made independent individual contributions to a joint action (low coordination condition) or made contributions that were tightly linked (high coordination condition).…”
Section: Uncertainty Reduction and The Sense Of Joint Agencymentioning
confidence: 99%